2005
DOI: 10.1191/1078155205jp149oa
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of standardized chemotherapy order forms on prescribing errors and anti-emetic cost

Abstract: SCOFs significantly reduced serotonin antagonist anti-emetic cost and prescribing error rate over a four-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 63 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Clinically, vomiting and nausea are frequently observed with the use of cytotoxic chemotherapy agents (e.g., Ettinger et al, 2008; Hesketh, 2008). Antiemetic drugs are not always effective for controlling emesis, can affect the efficacy of other treatments, pose potential health risks, and are expensive (Aapro, 2002; Candiotti et al, 2007; Llanes et al, 2006; Parsons et al, 2000; Sano et al, 2005; Twycross, 1994; Zhang et al, 2006a; Zhang et al, 2006b). Therefore, it is important to find better ways to control these side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, vomiting and nausea are frequently observed with the use of cytotoxic chemotherapy agents (e.g., Ettinger et al, 2008; Hesketh, 2008). Antiemetic drugs are not always effective for controlling emesis, can affect the efficacy of other treatments, pose potential health risks, and are expensive (Aapro, 2002; Candiotti et al, 2007; Llanes et al, 2006; Parsons et al, 2000; Sano et al, 2005; Twycross, 1994; Zhang et al, 2006a; Zhang et al, 2006b). Therefore, it is important to find better ways to control these side effects.…”
Section: Introductionmentioning
confidence: 99%
“…'s quality improvement project to reduce medication errors 96 and Sano et al on standardized chemotherapy order forms to reduce errors in the prescribing of antineoplastic medication. 91 Six studies (21%) addressed more than one issue of suboptimal use of medicines. 86,88,91,93,94,98 No study evaluated insufficient prescribing of low-cost generics.…”
Section: Resultsmentioning
confidence: 99%
“…91 Six studies (21%) addressed more than one issue of suboptimal use of medicines. 86,88,91,93,94,98 No study evaluated insufficient prescribing of low-cost generics. There was approximately a 50:50 split on whether studies were specific to a disease area or generic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported a reduction in medication errors [6][7][8][9] and improvement in the completeness of prescriptions, 9,10 as well as greater adherence to institutional policies and guidelines [11][12][13] and increased efficiency with the use of preprinted medication order forms. Several authors have reported a reduction in medication errors [6][7][8][9] and improvement in the completeness of prescriptions, 9,10 as well as greater adherence to institutional policies and guidelines [11][12][13] and increased efficiency with the use of preprinted medication order forms.…”
Section: Management Consultationmentioning
confidence: 99%